Advances in Image and Graphics Technologies 11th Chinese Conference, IGTA 2016, Beijing, China, July 8-9, 2016, Proceedings - Tan, Tieniu; Wang, Guoping; Wang, Shengjin; Liu, Yue; Yuan, Xiaoru; He, Ran; Li, Sheng (Communications in Computer and Information Science,, 2016)
This book constitutes the refereed proceedings of the 11th Chinese Conference on Image and Graphics Technologies and Applications, IGTA 2016, held in Beijing, China in July 2016. The 27 papers presented were carefully reviewed and selected from 69 submissions. They provide a forum for sharing progresses in the areas of image processing technology; image analysis and understanding; computer vision and pattern recognition; big data mining, computer graphics and VR; as well as image technology applications.